(untitled) (Jurnal Arsitektur ARCADE, 2026)
Urban economic growth causes mobility problems and increases emissions. However, research that addresses smart mobility by utilizing the development of information, communication, and technology (ICT) to monitor mobility and maximize the role of infrastructure needs to be further researched to support the Sustainable Development Goals 2030 Program. This research compares the impact of traffic density and emission production from conventional mobility concepts with the smart mobility concept which utilizes the Eco-Routing Navigation System and Vehicle License Plate System as part of ICT. It was found that the density of private vehicles decreased by ± 50%. The average density of light vehicles (LV) decreased from 1,304 pcu/hour to 652 pcu/hour and motorcycles (MC) from 1960 pcu/hour to 980 pcu/hour. Similarly, CO, HC, and CO2 levels decreased by 55.8% from 34.8 kg/km to 19.44 kg/km, HC by 53.73% from 0.67 kg/km to 0.36 kg/km, and CO2 by 52.5% from 4,226 kg/km to 2,218.92 kg/km. Traffic congestion causes congestion and emissions. The application of Smart Mobility collaborated with ICT successfully controls mobility by reducing the volume of vehicles and utilizing public transportation infrastructure so that emissions can be reduced.